2016
DOI: 10.1093/chromsci/bmw191
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Morin inMaclura cochinchinensisHeartwood by HPLC

Abstract: The HPLC-DAD method was developed to determine morin content in Maclura cochinchinensis Corner heartwood extract. The chromatographic separation was performed using a Hypersil BDS C18 column, isocratic solvent system of 0.5% acetic acid in water:acetonitrile (80:20) with 1.0 mL/min flow rate and detected at 355 nm. The standard curve of morin was linear in the range of 7-905 μg/mL. The method was precise with intra-day relative standard deviation (RSD) of lower than 1% and 2.06% for inter-day RSD. The method a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 10 publications
0
18
0
1
Order By: Relevance
“…The results revealed that there were at least seven phytophenols, including five flavonoids (morin, rutin, quercetin, isoquercitrin and luteolin) and two non-flavonoids (chlorogenic acid and maclurin). Among them, maclurin and morin can be found only in the Moraceae family, and they are regarded as marker components of the Moraceae family [ 16 18 ]. However, maclurin has been evaluated in our previous study [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results revealed that there were at least seven phytophenols, including five flavonoids (morin, rutin, quercetin, isoquercitrin and luteolin) and two non-flavonoids (chlorogenic acid and maclurin). Among them, maclurin and morin can be found only in the Moraceae family, and they are regarded as marker components of the Moraceae family [ 16 18 ]. However, maclurin has been evaluated in our previous study [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Kulit batangnya berwarna abu-abu muda sampai kecokelatan, daunnya berbentuk elips, bergerombol, dan memiliki buah berukuran cukup besar (Roemantyo, 1991 (Swargiary & Ronghang, 2013). Flavonoid utama dalam kayu Tegeran adalah morin yang memberi warna kuning pada sutera (Kongkiatpaiboon, et al, 2016;Septhum, et al, 2007).…”
Section: Pendahuluanunclassified
“…There are several analytical methods including HPLC , GC , TLC , CE , MEKC , and electrochemical methods for the separation of morin in various samples.…”
Section: Introductionmentioning
confidence: 99%
“…In the modern chemical analysis, sample preparation is a significant important step to isolate and/or preconcentrate the trace concentration level of analytes, especially in the samples characterized by the complicated matrices. Traditional sample preparation methods to analyze flavonols are basically based on LLE and SPE . However, these methods are not suitable to routine analyze the food products due to their high consumption of organic solvents, time‐consuming process, and high sample volume requirements.…”
Section: Introductionmentioning
confidence: 99%